Field lab Sme competitiveness - internationalization strategy: egg electronics - Lopes, Beatriz Alexandre (2021)
With the purpose of finding the most promising country for EGG Electronics to internationalize is business to, an In-Depth Analysis for the top five countries was conducted. Within this document you can find a thorough study of Luxembourg, a potential country that EGG should consider expanding to.For that analysis, four dimensions were considered: the quality of contacts in the country, the market sales potential, the competitive environment and the market entry conditions. Finally, to reach a sustained decision, a framework was developed in order to compare Luxembourg with the remaining countries and understand which one would be the go-to country for EGG.